If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(c + -4) + 3 = 2 + c + -39 Reorder the terms: 10(-4 + c) + 3 = 2 + c + -39 (-4 * 10 + c * 10) + 3 = 2 + c + -39 (-40 + 10c) + 3 = 2 + c + -39 Reorder the terms: -40 + 3 + 10c = 2 + c + -39 Combine like terms: -40 + 3 = -37 -37 + 10c = 2 + c + -39 Reorder the terms: -37 + 10c = 2 + -39 + c Combine like terms: 2 + -39 = -37 -37 + 10c = -37 + c Add '37' to each side of the equation. -37 + 37 + 10c = -37 + 37 + c Combine like terms: -37 + 37 = 0 0 + 10c = -37 + 37 + c 10c = -37 + 37 + c Combine like terms: -37 + 37 = 0 10c = 0 + c 10c = c Solving 10c = c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 10c + -1c = c + -1c Combine like terms: 10c + -1c = 9c 9c = c + -1c Combine like terms: c + -1c = 0 9c = 0 Divide each side by '9'. c = 0 Simplifying c = 0
| 2w-4-4w= | | x^2+9=-14 | | -21+7n=6(4n+5) | | -21+7n=6(4n++5) | | -8+3k=k-2k | | 4x+5x=108 | | 3x+x=39.2 | | 5-3x=13+5x | | B=135(.01743*.5)+(.0078*.0125) | | x+5-2x=-10 | | 8n^2+4n-24=0 | | -7x+40=5x-8(6x+4) | | x^2+x=20 | | -x-22=6-2x | | 9+6x(8-5)= | | x^2=45 | | 30+16x=75-6x | | (6m-7)6= | | 5k+7(1-3k)=23 | | -3x=10-x^2 | | 3(w-2)=-6 | | 32z+11-28z=50+2z-(-1) | | d(d-1)= | | x^2=212 | | -5x-4(-3x-6)=59 | | -3y-12=5y+12 | | 3+(2x+5)=6(x+1)+6 | | 4x-5=12x | | 40-3d=3y+10 | | x*2=8x | | -6(-4y)-13(2y)+y=-18 | | 7(3y-2)-7=0 |